Nd:YAG Laser in the Treatment of Nail Psoriasis: Clinical and Dermoscopic Assessment - Yasmin Hesham Ali Elwan (Mattioli1885, 2021)
Background: The Nd:YAG laser has emerged as a promising modality for the management of nail psoriasis owing to its ability for deep penetration of the skin surface, which has the advantage of destroying deep vessels.